HABP2 is a Novel Regulator of Hyaluronan-Mediated Human Lung Cancer Progression - Mirzapoiazova, Tamara; Mambetsariev, Nurbek; Lennon, Frances E.; Mambetsariev, Bolot; Berlind, Joshua E.; Salgia, Ravi; Singleton, Patrick A. (Frontiers in Oncology, 2015)
Background: Lung cancer is a devastating disease with limited treatment options. Many lung cancers have changes in their microenvironment including upregulation of the extracellular matrix glycosaminoglycan, hyaluronan (HA), which we have previously demonstrated can regulate the activity of the extracellular serine protease, Hyaluronan Binding Protein 2 (HABP2). This study examined the functional role of HABP2 on HA-mediated human lung cancer dynamics. Methods: Immunohistochemical analysis was performed on lung cancer patient samples using anti-HABP2 antibody. Stable control, shRNA and HABP2 overexpressing human lung adenocarcinoma cells were evaluated using immunoblot analysis, migration, extravasation and urokinase plasminogen activator (uPA) activation assays with or without high molecular weight HA (HMW-HA) or low molecular weight HA (LMW-HA). In human lung cancer xenograft models, primary tumor growth rates and lung metastasis were analyzed using consecutive tumor volume measurements and nestin immunoreactivity in nude mouse lungs. Results: We provide evidence that HABP2 is an important regulator of lung cancer progression. HABP2 expression was increased in several subtypes of patient non-small cell lung cancer samples. Further, HABP2 overexpression increased LMW-HA-induced uPA activation, migration and extravasation in human lung adenocarcinoma cells. In vivo, overexpression of HABP2 in human lung adenocarcinoma cells increased primary tumor growth rates in nude mice by ~2 fold and lung metastasis by ~10 fold compared to vector control cells (n=5 per condition). Conclusions: Our data suggests a possible direct effect of HABP2 on uPA activation and lung cancer progression. Our observations suggest that exploration of HABP2 in non-small cell lung carcinoma merits further study both as a diagnostic and therapeutic option.